4D printing of reprogrammable liquid crystal elastomers with synergistic photochromism and photoactuation - Chen, Mei (2023)
4D printing of liquid crystal elastomers (LCEs) via direct ink writing has opened up great opportunities to create stimuli-responsive actuations for applications such as soft robotics. However, most 4D-printed LCEs are limited to thermal actuation and fixed shape morphing, posing a challenge for achieving multiple programmable functionalities and reprogrammability. Here, a 4D-printable photochromic titanium-based nanocrystal (TiNC)/LCE composite ink is developed, which enables the reprogrammable photochromism and photoactuation of a single 4D-printed architecture. The printed TiNC/LCE composite exhibits reversible color-switching between white and black in response to ultraviolet (UV) irradiation and oxygen exposure. Upon near-infrared (NIR) irradiation, the UV-irradiated region can undergo photothermal actuation, allowing for robust grasping and weightlifting. By precisely controlling the structural design and the light irradiation, the single 4D-printed TiNC/LCE object can be globally or locally programmed, erased, and reprogrammed to achieve desirable photocontrollable color patterns and 3D structure constructions, such as barcode patterns and origami- and kirigami-inspired structures. This work provides a novel concept for designing and engineering adaptive structures with unique and tunable multifunctionalities, which have potential applications in biomimetic soft robotics, smart construction engineering, camouflage, multilevel information storage, etc.